Current Status and Potential of Moringa oleifera Leaf as an Alternative Protein Source for Animal Feeds - Su, Bin; Chen, Xiaoyang (Frontiers in Veterinary Science, 2020)
The increased consumption of livestock, poultry, and fish products in people's diet threatens to drive production toward the use of more and more conventional crops in animal feeds. In this context, alleviating the tightening grain crop supply and ensuring the healthy development of animal husbandry through innovations in protein feedstuff production remain considerable challenges. Moringa oleifera is a miracle tree species with abundant nutrients, high protein biological value, and good feeding effect. As a new protein feedstuff, M. oleifera has great potential in alleviating the feeding crisis. Here, we review available literature regarding the characterization of M. oleifera in the field of animal husbandry in terms of nutrient content, digestion, and absorption characteristics, and feeding effects and present current challenges in using M. oleifera as animal feed.